3D printing of hybrid MoS2-graphene aerogels as highly porous electrode materials for sodium ion battery anodes. (15th May 2019) - Brown, Emery; Yan, Pengli; Tekik, Halil; Elangovan, Ayyappan; Wang, Jian; Lin, Dong; Li, Jun
Abstract: This study reports a 3D freeze-printing method that integrates inkjet printing and freeze casting to control both the microstructure and macroporosity via formation of ice microcrystals during printing. A viscous aqueous ink consisting of a molecular MoS2 precursor (ammonium thiomolybdate) mixed with graphene oxide (GO) nanosheets is used in the printing process. Post-treatments by freeze-drying and reductive thermal annealing convert the printed intermediate mixture into a hybrid structure consisting of MoS2 nanoparticles anchored on the surface of 2D rGO nanosheets in a macroporous framework, which is fully characterized with FESEM, TEM, XRD, Raman spectroscopy and TGA. The resulting hybrid MoS2 -rGO aerogels are studied as anodes for sodium ion batteries. They present a high initial specific capacity over 429 mAh/g at C/3.3 rate in the potential range of 2.5–0.10 V (vs Na + /Na). The process involves both reversible 2 Na + insertion and slow irreversible conversion of MoS2 to metallic Mo. At higher rates, the conversion reaction is suppressed and the electrode is dominated by fast Na + intercalation with good stability. This demonstrates that the 3D printing technology can be used as a processing technique to control the materials properties for energy storage. Graphical abstract: Unlabelled Image Highlights: MoS2 -reduced graphene oxide aerogels have been firstly printed with a three-dimensional freeze printing method. The hybrid structure consists of small MoS2 patches attached on larger two-dimensional rGO flakes in a macroporous framework. The hybrid aerogels are utilized for sodium ion battery anodes.